Особливості національної кухні слов’ян - Харахайчук, І. А. (ХНУРЕ, 2020)
The history of the formation of Slavic folk cuisine and the factors that influenced its formation. The influence of the geographical position and identity of peoples on the construction of culinary features. Differences of Slavic cuisine from other cuisines of the world. Features of Slavic cooking.
Keywords: культурне розмаїття; українознавство; традиції; культура